Democracy in the Age of Globalization and Mediatization - Kriesi, H.; Bochsler, D.; Matthes, J.; Lavenex, S.; Bühlmann, M.; Esser, F.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This book provides comprehensive coverage of the models of contemporary democracy; its social, cultural, economic and political prerequisites; its empirically existing varieties and its two major challenges - globalization and mediatization. The book also covers the global spread of democracy and its spread into supranational democracies.
Keywords: European Union; Comparative politics; Political sociology; Political science; Democracy; Globalization; European Union Politics; Comparative Politics; Political Sociology; Political Science; Democracy; Globalization